2022
DOI: 10.1002/cbin.11838
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin‐mediated autophagy activates exosome release of rat nucleus pulposus cells by positively regulating Rab8a via the PI3K/PTEN/Akt pathway

Abstract: To provide a basis for promising exosome‐based therapies against intervertebral disc degeneration (IDD), our present research aimed to identify a mechanism underlying the vesicle release from nucleus pulposus cells (NPCs). Scutellarin (SC) is a natural chemotherapeutic agent isolated from Erigeron breviscapus with a variety of biological activities. Here, we observed the significantly elevated autophagy levels in rat NPCs under the stimulation of SC, leading to a concomitant enhancement of intracellular vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated that MBVs can fuse with lysosomes and be protected from degradation, and exosomes are then released by lysosomal exocytosis [ 44 ]. In addition, scutellarin activates autophagy by acting on the PI3K/PENT/Akt pathway, which upregulates the expression of Rab8a and promotes the release of exosomes [ 45 ]. Regarding the mechanism by which mTORC1 regulates the release of exosomes, mTORC1 regulates the fusion of MVBs with the plasma membrane through Rab27A in HeLa cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that MBVs can fuse with lysosomes and be protected from degradation, and exosomes are then released by lysosomal exocytosis [ 44 ]. In addition, scutellarin activates autophagy by acting on the PI3K/PENT/Akt pathway, which upregulates the expression of Rab8a and promotes the release of exosomes [ 45 ]. Regarding the mechanism by which mTORC1 regulates the release of exosomes, mTORC1 regulates the fusion of MVBs with the plasma membrane through Rab27A in HeLa cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%